EVALUATION OF THE OCHSENBEIN-LUEBKE FLAP TECHNIQUE IN PERIAPICAL SURGERY AT PUNJAB DENTAL HOSPITAL LAHORE PAKISTAN - Mushtaq, Iram; Malik, Arshad (Journal of Ayub Medical College Abbottabad, 2003)
Background: There have been no direct studies comparing the Trapezoidal flap with the Ochsenbein-Luebke flap in endodontic surgery. The present study is aimed to provide an insight into the relative performances of these two procedures. Methods: This comparative study, carried out at Punjab Dental Hospital Lahore Pakistan from May to October 1998, involved 120 patients (60 in each group). Evaluation of technique(s) involved assessment of intra-operative technical considerations as well as postoperative morbidity, healing and cosmetic results. Results: It was found that O-L flap is easy to reflect, has good visibility, less bleeding duration and is easy to handle during surgery. Stitches are less time consuming, there is less tearing, better cosmetic result and no recession of gingiva. However more studies should be done to evaluate the procedure in larger number of patients. Key Words: Flap design, Apicectomy, Trapezoidal Flap, Ochsenbein-Luebke Flap